Leaf δ- endotoxin content and performance of Bt cotton (Gossypium hirsutum) genotypes as influenced by fertility levels for target yields - Patil, A S Police; Chittarpur, B M; Udikeri, S S (The Indian Journal of Agricultural Sciences, 2012)
Two Bollgard I (cvs.MRC 6322 and MRC 6918) and two Bollgard II (cvs.MRC 7351 and MRC 7201) hybrids were supplied with three fertilizer levels (145:39:99, 181:49:124 and 217:59:148 NPK kg/ha, respectively1) targeted for 2.0, 2.5 and 3.0 tonnes/ha of seed cotton yield. d- Endotoxin content was higher in Bollgard II hybrids and MRC 6322 was comparable and the toxin content increased with increase in fertilizer level. However, the number of bad opened bolls differed among genotypes and it followed the total number of bolls rather than d- endotoxin content. Thus, the study brings two important points. First one is that in the selection of Bollgard I or Bollgard II hybrids, the intensity of population of pest in question matters most. And, secondly targeted yields set in the study were easily achieved and often exceeded. Hence, it is possible to achieve target yield of 3.0 tonnes/ha using desired level of fertilizer in most of the Bt hybrids, and this point needs emphasis as cotton is a commercial crop and for farmer monetary returns matter most.